Gut microbiome and human health: Exploring how the probiotic genus Lactobacillus modulate immune responses - Rastogi, Sonakshi; Singh, Aditi (Frontiers in Pharmacology, 2022)
The highest density of microbes resides in the human gastrointestinal tract, known as the “Gut microbiome”. Of note, the members of the genus Lactobacillus that belong to phyla Firmicutes are the most important probiotic bacteria of the gut microbiome. These gut-residing lactobacillus species not only communicate with each other but also with the gut epithelial lining to balance the gut barrier integrity, and mucosal barrier defense and ameliorate the host immune responses. The human body suffers from several inflammatory diseases affecting the gut, lungs, heart, bone, or neural tissues. Mounting evidence supports the significant role of lactobacillus spp. and their components (such as metabolites, peptidoglycans, and/or surface proteins) in modulating immune responses, primarily through the exchange of immunological signals between the gastrointestinal tract and distant organs. This bidirectional crosstalk which is mediated by lactobacilli spp. promotes anti-inflammatory response, thereby supporting the improvement of symptoms pertaining to asthma, chronic obstructive pulmonary disease (COPD), neuroinflammatory diseases (such as multiple sclerosis, Alzheimer's disease, Parkinson's disease), cardiovascular diseases, inflammatory bowel disease (IBD), and chronic infections in patients. The metabolic disorders, obesity, and diabetes are characterized by low-grade inflammation. Genus Lactobacillus alleviates metabolic disorders by regulating the oxidative stress response and inflammatory pathways. Osteoporosis is also associated with bone inflammation and resorption. The lactobacillus spp. and their metabolites act as powerful immune cell controllers and exhibit a regulatory role in bone resorption and formation, supporting bone health. Thus, this review demonstrated the mechanisms and summarized the evidence of the benefit of lactobacillus spp. in alleviating inflammatory diseases pertaining to different organs from animal and clinical trials. The present narrative review explores in detail the complex interactions between the gut-dwelling lactobacillus spp. and the immune components in distant organs to promote the host’s health.